Aircraft spin characteristics with high-alpha yawing moment asymmetry. (December 2018) - Malik, Bilal; Akhtar, Suhail; Masud, Jehanzeb
This paper analyzes the open-loop spin dynamics of a fighter configuration that exhibits yawing moment asymmetry at high angles of attack. High-fidelity aerodynamic model, in a look-up-tables form, is developed using the experimental data from static, coning, and oscillatory coning rotary balance wind tunnel tests. As a first step, all attainable equilibrium spin modes along with their sensitivity to control settings are predicted. Investigation of the dynamic characteristics of the predicted spin modes is performed using six degrees-of-freedom time history simulations, which showed that both, right and left flat spins are oscillatory and divergent. Influence of high-alpha yawing moment asymmetry on the spin recovery piloting strategies with control inputs is also studied with six degrees-of-freedom time history simulations. Our studies reveal that the proposed spin recovery strategies effectively reduce the recovery time for the left flat spins. However, aircraft's inherent tendency to yaw rightwards due to high-alpha yawing moment asymmetry renders proposed spin recovery strategies ineffective in accelerating the recovery of the right flat spins.